Pengaruh Lokasi,Harga dan Word of Mouth Terhadap Keputusan Pembelian pada Pesenjama Coffee Medan - Nurhasanah Putri; Roni, Shofan (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine the influence of location, price, and Word of mouth on purchasingdecisions at Pesenjama Coffee Medan. The background of this research is based on the increasinglyintense competition in the culinary business, particularly in the Marelan Raya area, as well as thedecline in Pesenjama Coffee’s sales during the 2020–2024 period. This research uses a quantitativemethod with an associative approach. The population consists of all Pesenjama Coffee consumers,while the sample was determined using data were collected through questionnaires and analyzedusing multiple linear regression with The assistance of SPSS.The results indicate that partially, thelocation variable has a positive and significant effect on purchasing decisions. The price variablealso has a positive and significant effect on purchasing decisions. Likewise, Word of Mouth has apositive and significant effect on purchasing decisions. Simultaneously, location, price, and Wordof Mouth have a positive and significant influence on purchasing decisions at Pesenjama CoffeeMedan.It can be concluded that consumer purchasing decisions at Pesenjama Coffee are stronglyinfluenced by a strategic and accessible location, prices that are in line with quality and consumerpurchasing power, as well as positive word of mouth formed through customer experiences. Thisresearch is expected to serve as an evaluation material for Pesenjama Coffee’s management informulating more effective marketing strategies to increase consumer purchase intention.